Edukasi Dampak Penggunaan Gadget terhadap Anak Sekolah Dasar di Pedesaan - Hayatun Nufus; Nailul Authar Ms; Muhammad Alfi Raihansyah; Khairul Maulidi; Elly Susanti; Ibnu Phonna Nurdin (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The use of gadgets in elementary school children is alarming. Prolonged use can lead to negative things for the growth and development of elementary school children. This service aims to realize the golden generation in 2045 by providing education to elementary school children about the impact of gadget use. There are 3 main focuses of the training that will be carried out, namely: Understanding and definition of gadget use, positive and negative impacts of gadget use, and minimizing gadget use. These three main activities are important activities that are followed by elementary school children. The results showed that the students were very enthusiastic and eager to participate in this educational activity. They actively asked questions and discussed the impact of gadgets. Students in this class showed commitment to apply the tips and strategies taught in the educational activities. They promised to reduce their gaming time, choose positive content, and interact more with friends and family. The education program also received a positive response from the school principal and teachers. The headmaster gave high appreciation for the initiative of the academician students in conducting this education. collaboration between the academician and the school is needed in order to realize the sustainability of the program that has been implemented.